The Game Of 'What Falls' Through Information Services At Senior High School 1 Kurun, Kuala Kurun - Suriatie, Mimi; Sangalang, Oktamia Karuniaty; Pangestie, Esty Pan; Feronika, Nopi (Suluh: Jurnal Bimbingan dan Konseling, 2023)
A teacher is highly expected for the benefit of effectiveness and efficiency of Guidance and Counseling services in schools. Teachers can also act as mentors for their students. One of the government's policies is to promote guidance and counseling in schools to assist the educational process and the quality of human resources. The purpose of this study " is to know teachers' participation in using the game "What Falls" through information services at Senior High School 1 Kurun, Kuala Kurun. "The sample consisted of 51 teachers in the school. The main data collection tool uses the Check List technique, namely, a way to obtain data by making a list of questions addressed to all teachers at Senior High School 1 Kurun, Kuala Kurun. Researchers use percentage calculations to analyze the data to test the reality that there is teacher participation in schools in implementing group guidance services. The results showed that almost all of the components of the objectives in the study were carried out at a fairly high percentage of 100% by the teachers at the school. This means teachers participate in and support information services at Senior High School 1 Kurun, Kuala Kurun.